Racial/Ethnic Differences in Labor Induction in a Contemporary US Cohort: A Retrospective Cohort Study - Singh, Jasbir; Reddy, Uma M.; Huang, Chun-Chih; Driggers, Rita W.; Landy, Helain J.; Grantz, Katherine L. (American Journal of Perinatology, 2018)
Objective To examine labor induction by race/ethnicity and factors associated with disparity in induction.Study Design This is a retrospective cohort study of 143,634 women eligible for induction ≥24 weeks' gestation from 12 clinical centers (2002–2008). Rates of labor induction for each racial/ethnic group were calculated and stratified by gestational age intervals: early preterm (240/7–336/7), late preterm (340/7–366/7), and term (370/7–416/7 weeks). Multivariable logistic regression examined the association between maternal race/ethnicity and induction controlling for maternal characteristics and pregnancy complications. The primary outcome was rate of induction by race/ethnicity. Inductions that were indicated, non-medically indicated, or without recorded indication were also compared.Results Non-Hispanic black (NHB) women had the highest percentage rate of induction, 44.6% (p < 0.001). After adjustment, all racial/ethnic groups had lower odds of induction compared with non-Hispanic white (NHW) women. At term, NHW women had the highest percentage rate (45.4%) of non-medically indicated or induction with no indication (p < 0.001).Conclusion Compared with other racial/ethnic groups, NHW women were more likely to undergo non-medically indicated induction at term. As labor induction may avoid the occurrence of stillbirth, whether this finding explains part of the increased risk of stillbirth for NHB women at term merits further research.
Keywords: disparity; labor; induction; obstetrics; race; ethnicity